A Comprehensive Strategy for Laser Corneal Refractive Surgery during the COVID-19 Epidemic in a Tertiary Teaching Hospital in Wenzhou, China - Jia Zhang; Ioannis M. Aslanides; Vasileios Selimis; Nan-Ji Lu; Wei-Jie Liu; Hong-Xiao Jiang; Chao Zhang; Chen-Chen Xu; Qin-Mei Wang; Jia Qu; Shi-Hao Chen (Journal of Ophthalmology)
The novel coronavirus pneumonia COVID-19 is caused by the novel coronavirus SARS-CoV-2, which is highly contagious, has a long incubation period, and can be detected in patients’ tears and conjunctival secretions. In this study, we describe our experience regarding the necessary protective measures that need to be taken during ophthalmic examination and treatment. The authors reviewed the clinical work arrangements during the epidemic situation at the Eye Hospital of Wenzhou Medical University in China and analyzed the prevention and control measures that were applied during the laser corneal refractive surgery process. The comprehensive protection protocol, which was established throughout the entire process, included both horizontal (medical staff-patient, medical staff-medical staff, and patient-patient) and vertical (preoperative, intraoperative, and postoperative transmission assessment) approach and was mainly focused on strengthening the protection against potential aerosol transmission that may occur during intraocular pressure measurements and laser ablation. The described and proposed protocol, along with the further guidelines followed by the medical personnel, proved to be efficacious and contributed significantly to the control of the COVID-19 outbreak and the protection of both the patients and the medical staff.